Characterization of Cuticle Layer of Ilex latifolia - Jun-ichi Azuma; Shuntaro Tsubaki; Rike Yudianti; Myrtha Karina (Masyarakat Peneliti Kayu Indonesia, 2010)
Cuticular membranes were isolated from the upper and lower surfaces of Ilex latifolia leaves and their morphological, chemical compositional and mechanical properties were characterized. The upper cuticular membrane contained 18.6% wax, 53.5% cutin and 17.5% cutan with low contaminating carbohydrates (10.4%), while the lower cuticular membrane had the values of 17.9%, 49.2%, 15.8% and 17.1%. Both membranes were rich in aliphatic CH2 groups, and the main monomer of the cutin in the upper cuticular membrane was 9(10),18-dihydroxyhexadecanoic acid while 9,10,18-trihydroxyoctadecanoic acid in the lower membrane. Mechanical analyses indicate clear orientation differences in breaking stress and strain between the two membranes with higher breaking stress in the upper cuticular membrane and in the longitudinal direction parallel to the midvein. Additive such as a cellulosic hydrogel from Salvia viridis to make a composite influenced the mechnical properties of the cuticular membranes. Mechanical properties of the isolated cuticular membranes may be more influenced by their morphological properties than chemical compositions; thick and smooth structure of the upper cuticular membrane, while wrinkled and scattered stoma-rich structure of the lower cuticular membrane.